Respon Penurunan Konsentrasi Logam Berat Kromium (Cr) dan Pertumbuhan Mikroalga Chlorella vulgaris pada Media Kultur - Sulistya_Dewi, Endah Rita (Prosiding KPSDA, 2015)
This study aims to evaluate the response of a decrease in the concentration of Cr in the culture medium and to determine the effect of Cr concentration on the growth of Chlorella vulgaris. This study used a completely randomized design (CRD) with 4 treatments and 3 repetitions. These treatments include, K treatment (control), treatment of Cr 1 (addition of chromium concentration of 1 mg / L), treatment of Cr 3 (addition of chromium concentration of 3 mg / L) and treatment of Cr 5 (addition of chromium concentration of 5 mg / L). Each sample was analyzed by AAS. Analysis of the data is using analysis of variance followed by Duncan test. The results of the analysis of metal concentrations decrease of Cr in the culture medium is Cr 3 (1.2834 mg / l), Cr 1 (0.4360 mg / l), Cr 5 (0.4276 mg / l), and K (0.0126 mg / l). Results of analysis of variance F test showed that Chlorella vulgaris gives highly significant effect on decreasing the concentration of Cd metal. While the results of the growth of Chlorella vulgaris during culture is Cr 3 (909.55 cells / ml), Cr 1 (864.28 cells / ml), Cr 5 (659.20 cells / ml), and K (647.15 cells / ml). Results of analysis of variance showed that different concentrations of Cd metal gives highly significant effect on the growth of Chlorella vulgaris. The conclusion is Chlorella vulgaris has the ability as bioremediator chromium with different concentrations, as shown by the reduction of Cd content in the culture medium. Chlorella vulgaris has a polyamine whose role is to protect or as a protection in a contaminated environment.